UTILIZATION OF ARTIFICIAL INTELLIGENCE IN MARKETING INFORMATION SYSTEMS AND STRATEGIES - Rakhmawati; Yudhi Prasetya Mada (International Journal of Innovations in Engineering Research and Technology, 2025)
This research study develops a model that integrates marketing information systems and strategic levels and examines the implementation of these systems at each strategic level. To achieve the first objective, the role played by the CEO or manager at each strategic level and the specific information systems required for each case are the starting points of the study. To achieve the second objective, a qualitative method is applied, and the technique used is in-depth interviews. The study shows that companies do use all four marketing information systems, although with different emphases, depending on the strategic level. Artificial Intelligence (AI) has developed rapidly and penetrated various aspects of life, from simple applications on mobile phones to complex systems in industry and scientific research. In general, AI is defined as the ability of a computer system to imitate human cognitive functions, such as learning, reasoning, and problem solving. The development of AI is driven by the availability of abundant data (big data), increasing computing power, and advances in algorithms.